Landmarks in the Development of Historical Criticism Among Muslims and Westerners - Mohammed, aissaoua (The Algerian Historical Journal, 2026)
This article discusses pivotal points in the evolution of historical criticism among Muslims and Westerners. It highlights, in some detail, the innovative mechanisms employed in the process of criticism practiced by Muslims and Westerners across various historical eras. The objective is to transition from the stage of reading and quoting various historical documents and texts to the phase of examination and verification. This underscores the significance of this process, as it is crucial for reaching historical truth and distinguishing accurate news from fabricated ones. Thus, the ability to comprehend historical texts, analyze them, interpret them, and extract facts from them is only achieved by researchers through the practice of historical criticism.